On the origin of UV-dim stars: a population of rapidly rotating shell stars? - Martocchia, Silvia; Bastian, Nate; Saracino, Sara; Kamann, Sebastian (Monthly notices of the Royal Astronomical Society, 2023)
The importance of stellar rotation in setting the observed properties of young star clusters has become clearer over the past decade, with rotation being identified as the main cause of the observed extended main sequence turn-off (eMSTO) phenomenon and split main sequences. Additionally, young star clusters are observed to host large fractions of rapidly rotating Be stars, many of which are seen nearly equator-on through decretion discs that cause self-extinction (the so called ‘shell stars’). Recently, a new phenomenon has been reported in the ∼1.5 Gyr star cluster NGC 1783, where a fraction of the main-equence turn-off stars appears abnormally dim in the UV. We investigate the origin of these ‘UV-dim’ stars by comparing the UV colour-magnitude diagrams of NGC 1850 (∼100 Myr), NGC 1783 (∼1.5 Gyr), NGC 1978 (∼2 Gyr), and NGC 2121 (∼2.5 Gyr), massive star clusters in the Large Magellanic Cloud. While the younger clusters show a non-negligible fraction of UV-dim stars, we find a significant drop of such stars in the two older clusters. This is remarkable as clusters older than ∼2 Gyr do not have an eMSTO, thus a large populations of rapidly rotating stars, because their main-sequence turn-off stars are low enough in mass to slow down due to magnetic braking. We conclude that the UV-dim stars are likely rapidly rotating stars with decretion discs seen nearly equator-on (i.e. are shell stars) and discuss future observations that can confirm or refute our hypothesis.
Online veröffentlicht: 6. Februar 2023
Gesehen am 26.09.2023